Rancang Bangun Sistem Pemotong pada Mesin Pengupas dan Pemotong Kentang Spiral dengan Kapasitas 15 Kg/Jam - Syadilla Ega Maharani; Joko Setia Pribadi; Agus Santoso; Fadillah; Murni Handayani (Politeknik Negeri Cilacap, 2021)
Spiral potato peeler and cutter is a machine used to assist the production process of a home-based bussiness in potato processing, starting from the peeling process to the cutting process carried out in one machine frame. The design and construction of the cutting system on spiral potato peeler and cutter machine with a capacity of 15 kg/hour has several objectives, namely being able to make detailed analisis of a spiral potato cutting machine, being able to calculate parts of the machine elements used in parts of the cutting system and being able to did spiral potato machine testing. The methode used in the preparation of this project report is through the VDI 2222 approach which begins with the plan, conceptual, design and completions stages.The results of the calculation of the cutting system elements on the spiral potato peeler and cutter machine include the large diameter of the shaft used is 12,7 mm, the use of 84 watt motor power and the capacity of the cutting system on the spiral potato cutting machine is 15,25 kg/hour.